Two useful trees abreast - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
International workshop on drying and improvement of shea and canarium Edited by C Kapseu & J Kayem, 2000. 463 pp. ISBN 2 911541 10 3 Département de Génie des Procédés École nationale supérieure des sciences agro-industrielles (ENSAI), 2000 Uni